Stop reconstruction with tagged tops - Plehn, Tilman; Spannowsky, Michael; Takeuchi, Michihisa; Zerwas, Dirk (Journal of high energy physics, 2010)
At the LHC combinatorics make it unlikely that we will be able to observe stop pair production with a decay to a semi-leptonic top pair and missing energy for generic supersymmetric mass spectra. Using a Standard-Model top tagger on fully hadronic top decays we can not only extract the stop signal but also measure the top momentum. To illustrate the promise of tagging tops with moderate boost we include a detailed discussion of our HEPTopTagger algorithm.